Emma's Character and the Language Power in the Fairclough's Critical Discourse Analysis Lens - Passandaran, Yossi M.; Sofiani, Yulia; Tiwiyanti, Leni (BRIGHT : A Journal of English Language Teaching, Linguistics and Literature, 2025)
Through an eye on the power dynamics in language, this study uses Fairclough's Critical Discourse Analysis (CDA) to analyze Emma's character in Jane Austen's Emma. The three-dimensional framework developed by Fairclough's text analysis, discourse practice, and sociocultural practice, is used in this research for analyzing how Emma's language both reflects and negotiates social hierarchy, gender roles, and power systems. Emma exhibits linguistic agency through her speech patterns, conversational dominance, and interactions with other characters, exposing both social limits and her self-determination. The results point out that Emma is influenced by the ideological frameworks of her day even though she occasionally uses discursive power. This research provides to a better understanding of how language acts as a tool for power and identity creation in literary discourse, particularly in regard to gender and class in Austen's works. By highlighting the importance of language in determining character interactions and social standing, this study advances literary discourse studies.